ENSURING THE LONG-TERM STABILITY OF DEEP CUTTING SLOPES FORMED BY CLAY SOILS ON REPUBLIC OF MOLDOVA ROADS - POLCANOV, Vladimir; POLCANOVA, Alina; CÎRLAN, Alexandru (Journal of Engineering Science (Chişinău))
The article presents research results on identifying the causes of landslide deformations along the M21 road, Brest-Chișinău-Poltava in the Republic of Moldova, using Maslov's physico-technical theory of creep, along with proposals for their stabilization. It highlights the geomorphological and geological characteristics contributing to landslide formation, focusing on the rheological properties of clayey soils. The studies included stability calculations based on laboratory investigations aimed at determining strength and rheological properties. Results demonstrated the dependence between soil moisture and structural cohesion, influencing landslide resistance and creep deformations. Proposed values for residual strength characteristics of clayey soils ensure long-term stability of deep excavation slopes without creep deformations, as well as values allowing economically feasible excavations with partial reduction of structural cohesion without compromising slope stability during operation.